High nature value farming systems in Europe: A dataset encompassing the environmental impact assessment of farms and extensive ruminant food productsFigshare - M. Torres-Miralles; P. Jeanneret; M. Lamminen; F. Joly; B. Dumont; H. Tuomisto; I. Herzon (Data in Brief)
High Nature Value (HNV) farming systems occur in areas where the major land use is agriculture and are characterized by their significance in promoting biodiversity and ecosystem services due to their extensive land use. Despite their importance for ecological and socio-economic resilience of rural regions, these systems are often overlooked in Life Cycle Assessment (LCA) studies due to challenges in data compilation, especially from small local farms and because of the diversity of production. To address this gap, we established an international collaborative network across Europe, involving professionals directly engaged with farmers, farmer associations, and researchers to collect data on HNV farms employing a developed questionnaire examining inputs and outputs, farm structures, and herd characteristics. Our dataset includes 41 farms and covers five European countries—Spain, France, Greece, Estonia, and Finland—spanning three bioregions of Mediterranean, Atlantic, and Boreal. Data, anonymised and integrated into a matrix, focus on such environmental impact indicators as greenhouse gas emissions (GHGs), biodiversity, land and water use, and fossil resource scarcity. We applied LCA using analytical tools such as the European Carbon Calculator (Joint Research Centre of the European Commission), OpenLCA 10.4., and the SALCA-BD expert system. Additionally, we utilised the LCA inventory Agribalyse 3.0 database to estimate the environmental footprint of four pivotal HNV products: goat cheese, cow milk, lamb, and beef. The main outcome is a unique and novel dataset for HNV farming systems, addressing critical gaps in available information. Our primary objective is to facilitate further investigations, empowering other researchers to expand and enhance their understanding of the environmental impact associated with HNV farming systems, drawing attention to a potential role of HNV farming systems in transitioning towards a more sustainable food production and consumption.